Leadership ethics - Ciulla, Joanne B.; Uhl-Biel, Mary; Werhane, Patricia H. (SAGE benchmarks in leadership, 2013)
Research into the topic of leadership ethics has grown and evolved gradually over the past few decades. This timely set arrives at an important moment in the subject's history. In a relatively new field, such a collection offers scholars more than articles on a topic; it also serves to outline the parameters of the field. Carefully structured over three volumes, the material runs through an understanding of the key philosophic and practical questions in leadership ethics along with a wide range of literature - from disciplines including philosophy, business and political science, to name a few- that speaks to these questions.